Laryngopharyngeal pH Monitoring in Patients With Idiopathic Pulmonary Fibrosis - Su, Yiliang; Shen, Li; Zhang, Fen; Jiang, Xing; Jin, Xiaofeng; Zhang, Yuan; Hu, Yang; Zhou, Ying; Li, Qiuhong; Li, Huiping (Frontiers in Pharmacology, 2021)
Background: Patients with idiopathic pulmonary fibrosis (IPF) often have irritating persistent dry cough. Possible correlations between dry cough and laryngopharyngeal reflux (LPR) remain unclear. Methods: 44 patients with IPF and 30 healthy individuals underwent 24-hour laryngopharyngeal pH monitoring. Ryan index score was calculated. Patients’ demographic and clinical data were collected. Results: 44 patients with IPF and 30 healthy individuals were included. The proportions of men and smokers were significantly higher in IPF group than control group (All P<0.01). The average laryngopharyngeal pH value for 24 hours was similar in the IPF (7.11 ± 0.08) group and control group (7.09 ± 0.06). According to the percentage duration of pH<6.5, pH6.5-7.5, and pH>7.5 in the overall measure duration, the patients were classified into three pH groups. In entire pH monitoring duration, the proportion of pH>7.5 group in IPF patients was higher than control group; at upright position, the proportion of pH>7.5 group in IPF patients was higher than control group; at supine position, the proportion of pH<6.5 group in IPF patients was higher than control group (All P<0.01). Seven patients had Ryan index score>9.41 at upright position. All patients had Ryan index score<6.79 at supine position. Four patients showed significantly higher and one patient had significantly lower average pH at coughing than the overall average pH (All P<0.05). Conclusions: Patients with IPF may have LPR. Basic and acidic LPR may likely occur at upright and supine position, respectively. Ryan index may not accurately reflect LPR in patients with IPF.